Cyclodextrin metal–organic framework by ultrasound-assisted rapid synthesis for caffeic acid loading and antibacterial application - Mofei Shen; Jianwei Zhou; Mohamed Elhadidy; Yunlei Xianyu; Jinsong Feng; Donghong Liu; Tian Ding (Ultrasonics Sonochemistry, 2022)
Cyclodextrin metal–organic framework by ultrasound-assisted rapid synthesis for caffeic acid (CA) loading and antibacterial application (U-CD-MOF) was successfully studied and this method shortened the preparation time to a few minutes. It was found that the ultrasonic power, reaction time and temperature would affect the morphology and size of the obtained crystal. Under the optimal conditions, U-CD-MOF had a cubic structure with uniform size of 8.60 ± 1.95 μm. U-CD-MOF was used to load the antibacterial natural product CA to form the composite (CA@U-CD-MOF) and the loading rate of CA@U-CD-MOF to CA could reach 19.63 ± 2.53%, which was more than twice that of γ-CD. Various techniques were applied to characterize the synthesized crystal, including Powder X-ray diffraction (PXRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), thermogravimetric analysis (TGA), and N2 adsorption. In addition, antibacterial tests were performed on the obtained crystal. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of CA@U-CD-MOF for Escherichia coli O157: H7 (E. coli O157: H7) were both 25 mg·mL−1, and the MIC for Staphylococcus aureus (S. aureus). was 25 mg·mL−1. The sustained release behavior of CA@U-CD-MOF to CA in ethanol fitted well to Higuchi model and the loading of CA was supported by molecular docking results. In general, U-CD-MOF was successfully achieved by ultrasound-assisted rapid synthesis and the obtained crystal was further evaluated for potential antibacterial application.